Common NFKBIL2 polymorphisms and susceptibility to pneumococcal disease: a genetic association study. - Chapman, S; Khor, C; Vannberg, F; Rautanen, A; Walley, A; Segal, S; Moore, C; Davies, R; Day, N; Peshu, N; Crook, D; Berkley, J; et al. (2010)
INTRODUCTION: Streptococcus pneumoniae remains a major global health problem and a leading cause of death in children worldwide. The factors that influence development of pneumococcal sepsis remain poorly understood, although increasing evidence points towards a role for genetic variation in the host's immune response. Recent insights from the study of animal models, rare human primary immunodeficiency states, and population-based genetic epidemiology have focused attention on the role of the proinflammatory transcription factor NF-κB in pneumococcal disease pathogenesis. The possible role of genetic variation in the atypical NF-κB inhibitor IκB-R, encoded by NFKBIL2, in susceptibility to invasive pneumococcal disease has not, to our knowledge, previously been reported upon. METHODS: An association study was performed examining the frequencies of nine common NFKBIL2 polymorphisms in two invasive pneumococcal disease case-control groups: European individuals from hospitals in Oxfordshire, UK (275 patients and 733 controls), and African individuals from Kilifi District Hospital, Kenya (687 patients with bacteraemia, of which 173 patients had pneumococcal disease, together with 550 controls). RESULTS: Five polymorphisms significantly associated with invasive pneumococcal disease susceptibility in the European study, of which two polymorphisms also associated with disease in African individuals. Heterozygosity at these loci was associated with protection from invasive pneumococcal disease (rs760477, Mantel-Haenszel 2 × 2 χ(2) = 11.797, P = 0.0006, odds ratio = 0.67, 95% confidence interval = 0.53 to 0.84; rs4925858, Mantel-Haenszel 2 × 2 χ(2) = 9.104, P = 0.003, odds ratio = 0.70, 95% confidence interval = 0.55 to 0.88). Linkage disequilibrium was more extensive in European individuals than in Kenyans. CONCLUSIONS: Common NFKBIL2 polymorphisms are associated with susceptibility to invasive pneumococcal disease in European and African populations. These findings further highlight the importance of control of NF-κB in host defence against pneumococcal disease.